2015
DOI: 10.1111/trf.13102
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive fetal genotyping of human platelet antigen‐1a using targeted massively parallel sequencing

Abstract: We have successfully established massively parallel sequencing as a novel reliable method for noninvasive genotyping of fetal HPA-1a alleles. This technique may also allow the safe detection of other fetal blood group polymorphisms frequently involved in FNAIT and hemolytic disease of the newborn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 33 publications
(37 reference statements)
2
38
0
1
Order By: Relevance
“…Assays for noninvasive prenatal testing to detect fetal HPA-1a DNA in maternal plasma have been developed and are in use in many research laboratories, but are not yet implemented in routine clinical practice in most countries 6872. Determination of paternal zygosity may be relevant.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Assays for noninvasive prenatal testing to detect fetal HPA-1a DNA in maternal plasma have been developed and are in use in many research laboratories, but are not yet implemented in routine clinical practice in most countries 6872. Determination of paternal zygosity may be relevant.…”
Section: Diagnosismentioning
confidence: 99%
“…The clinical outcome of ICH due to FNAIT is reported to be worse compared to neonatal ICH from other causes75,76 and may be connected to the typical locations of the bleedings in the brain. Severe neurological complications are found in 36%–68% of ICH cases24,26,77,78 and fetal or neonatal death due to ICH is reported in the range of 9%–46%24,57,68,79 when evaluated retrospectively. A large cohort study from the international No Intracranial Hemorrhage (NOICH) registry described 43 cases of ICH caused by FNAIT in depth and found that the majority of bleedings (54%) happened before the third trimester and 67% before 34 gestational weeks 77.…”
Section: Clinical Presentation and Outcomementioning
confidence: 99%
“…Background signals in the cfDNA sequencing reads were evaluated by the fraction of nonspecific alleles that did not belong to the known bi‐allelic system . As a result, the levels of nonspecific alleles were zero at most loci for the 34 maternal cfDNA samples, and the overall level of the background signals was detected with a mean (± SD) frequency of 1.02% (± 0.24%) with a range from 0.00% to 9.00% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1) at each locus with a minimum coverage of 1000×, as previously described [25,26]. As a result, the levels of non-specific alleles were zero at most A-SNP loci for the 20 maternal cfDNA samples, except for 58 loci with detectable nonspecific alleles (Table S3).…”
Section: Locus Performancementioning
confidence: 99%
“…Then, the overall level of the background signals was detected with a mean (±SD) frequency of 0.0028% (±0.049%), ranging from 0% to 1.6%. It is expected that an a priori defined cutoff value of 2% for paternally inherited foetal alleles was clearly separated from the background signals [26].…”
Section: Locus Performancementioning
confidence: 99%